Tobacco Workers Fight to Defend Their Jobs Against Huge Cigarette Tax Hikes - SUSAN STUNTZ (Tufts Archival Research Center, 2007)
Documents relating to the Labor Day promotion of labor, specifically Bakery, Confectionary, and Tobacco Workers International Union (BC&T) opposition to a tobacco tax. Includes cover memo from Susan Stuntz to Bob Lewis and Bob McAdam and a copy of the BC&T press releases and radio transcript. Urges Congress to push cost containment and progressive financing in lieu of raising tobacco tax. Predicts tobacco tax will cost many jobs, devastate Southern communities, and unfairly burden the working class.